Heart rate variability monitoring for the detection of delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage. Issue 7 (19th April 2020) - Bjerkne Wenneberg, Sandra; Löwhagen Hendén, Pia M.; Oras, Jonatan; Naredi, Silvana; Block, Linda; Ljungqvist, Johan; Odenstedt Hergès, Helena
Abstract : Background: Delayed cerebral ischemia (DCI) is a major cause of impaired outcome after aneurysmal subarachnoidal hemorrhage (aSAH). In this observational cohort study we investigated whether changes in heart rate variability (HRV) that precede DCI could be detected. Methods: Sixty‐four patients with aSAH were included. HRV data were collected for up to 10 days and analyzed offline. Correlation with clinical status and/or radiologic findings was investigated. A linear mixed model was used for the evaluation of HRV parameters over time in patients with and without DCI. Extended Glasgow outcome scale score was assessed after 1 year. Results: In 55 patients HRV data could be analyzed. Fifteen patients developed DCI. No changes in HRV parameters were observed 24 hours before onset of DCI. Mean of the HRV parameters in the first 48 hours did not correlate with the development of DCI. Low/high frequency (LF/HF) ratio increased more in patients developing DCI (β −0.07 (95% confidence interval, 0.12‐0.01); P = .012). Lower STDRR (standard deviation of RR intervals), RMSSD (root mean square of the successive differences between adjacent RR intervals), and total power ( P = .003, P = .007 and P = .004 respectively) in the first 48 hours were seen in patients who died within 1 year. Conclusion: Impaired HRV correlated with 1‐year mortality and LF/HF ratio increased more in patients developing DCI. Even though DCI could not be detected by the intermittent analysis of HRV used in this study, continuous HRV monitoring may have potential in the detection of DCI after aSAH using different methods of analysis.